2016
DOI: 10.1039/c6cc04210d
|View full text |Cite
|
Sign up to set email alerts
|

Rapid protein immobilization for thin film continuous flow biocatalysis

Abstract: A versatile enzyme immobilization strategy for thin film continuous flow processing is reported. Here, non-covalent and glutaraldehyde bioconjugation are used to immobilize enzymes on the surfaces of borosilicate reactors. This approach requires only ng of protein per reactor tube, with the stock protein solution readily recycled to sequentially coat >10 reactors. Confining reagents to thin films during immobilization reduced the amount of protein, piranha-cleaning solution, and other reagents by ~96%. Through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 44 publications
(70 reference statements)
0
43
0
Order By: Relevance
“…[5] Enzyme immobilization techniques include encapsulation in (in)organic microporous structures, attachment on functionalized supports, cross-linking, and coordination through ionic interactions. [5, 6]…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[5] Enzyme immobilization techniques include encapsulation in (in)organic microporous structures, attachment on functionalized supports, cross-linking, and coordination through ionic interactions. [5, 6]…”
mentioning
confidence: 99%
“…Conversely, encapsulation (or entrapment) and noncovalent immobilization often suffer from enzyme leakage, whereas covalent enzyme immobilization can lead to random attachment between the enzyme surface and the functional groups on the support, potentially decreasing the activity. [5]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial approach to immobilize proteins for continuous flow biocatalysis applied non-specific glutaraldehyde-based crosslinking to the reactor surface. [14] Although this generated a highly efficient continuous flow system for individual proteins, the method proved to be unworkable for creating the distinct enzyme zones envisioned for enzymatic assembly lines. Specifically, the relatively slow kinetics of this attachment method prevented confinement of each enzyme to a specific zone of the reactor.…”
mentioning
confidence: 99%
“…Third, alkaline phosphatase and phosphodiesterase are stable to vortexing and other potentially harsh conditions. [14] Lastly, the reaction had to take place along the length of the reactor; previous experiments had shown that alkaline phosphatase and phosphodiesterase have rapid catalytic activity. [12] …”
mentioning
confidence: 99%